The value of large-scale programmes in human genomics - Horn, Ruth; Kerasidou, Angeliki; Merchant, Jennifer; Bale, Mark; Banner, Natalie; Buchanan, James; Cambon-Thomsen, Anne; Chneiweis, Herve; Cividanes, Lene; Clarke, Angus; Kuiper, Janneke M. L.; Lewis, Celine; et al. (European journal of human genetics, 2025)
Large national genomic programmes have been created in many countries, including France, England and Germany, to advance the realisation of the potential genomic medicine holds to significantly contribute to society by improving health, and driving science, innovation and the economy. To reach this ambition, these programmes collect, manage and analyse big genomic datasets. While there is much talk about the promises, and hence the importance of genomics, there is little in-depth analysis of the actual contribution or value—here understood as benefits—of genomics for society at large. To explore the issue of the value of large-scale genomic programmes for society, UK-FR-D+ GENE held an international workshop focusing on a variety of levels—societal, economic, clinical, scientific, and population-wide level—at which such benefits might be observed. First, the broader societal implications of large genome programmes and their impact for public trust were discussed. Second, the meaning of fair and just allocation of public resources, based on considerations of the economic costs and benefits of genomic innovations, was examined. Third, the benefits of these innovations for stakeholders (clinicians, patients, and families) at the clinical level were investigated. Fourth, the scope and limitations of genomics at the scientific level were discussed. Finally, the potential of genomics to improve health at the population level was explored. Providing an insight into the benefits of large genomic programmes on various levels, the workshop concluded by defining several criteria that should be considered to ensure benefits for society when implementing large genomic programmes.
Gesehen am 13.10.2025